Microalgal Diet Influences the Nutritive Quality and Reproductive Investment of the Cyclopoid Copepod Paracyclopina nana - Dayras, Paul; Bialais, Capucine; Sadovskaya, Irina; Lee, Min-Chul; Lee, Jae-Seong; Souissi, Sami (Frontiers in Marine Science, 2021)
Copepods represent an interesting alternative or a complement live food to brine shrimps and rotifers commonly used in aquaculture. They constitute the natural prey of many fish species and therefore do not require a potential nutritional enrichment. But an optimization of the microalgal diets used to feed copepods is essential to improve their mass culture. This study examined the effects of seven microalgal diets, namely single-species diets of Rhodomonas salina (R), Tisochrysis lutea (T), and Pavlova lutheri (=Diacronema lutheri) (P), two-species diets (R + T, T + P and R + P), and a three-species diet (R + T + P), on the fatty acid and monosaccharide composition of the cyclopoid copepod Paracyclopina nana as well as its reproductive investment. Experiments were run during 15 days in 10-L beakers; starting with nauplii collected from a large 300-L batch culture. Copepods fatty acid contents were studied, particularly the relative amounts of docosahexaenoic acid (DHA) and eicosa-pentaenoic acid (EPA). The R + T, R and T diets induced the highest total fatty acid amount in copepods. R + T and R also generated the lowest DHA/EPA ratios in copepods due to high EPA contents. The highest value of total monosaccharides was found in copepods fed with R + T + P. Diets R + T and R induced the greatest prosome volumes and clutch volumes in ovigerous females. Both prosome volume and clutch volume in P. nana ovigerous females were correlated to the individual EPA amount. The results demonstrated that all diets including R. salina enhanced the productivity of P. nana in mass culture, particularly when combined with T. lutea. R. salina and T. lutea induced complementary fatty acid and monosaccharide profiles, confirming that R + T represents the best microalgae combination for productive culture of P. nana. Conversely, P. lutheri did not enhance the nutritional profile nor the fecundity of P. nana in the culture. This study is the first to demonstrate that R. salina is a suitable microalga for productive mass culture of P. nana for use as live food in aquaculture.